Is multiple-use forest management widely implementable in the tropics? - García Fernandez, C.; Ruíz Pérez, M.; Wunder, Sven (Elsevier, 2008)
Multiple-use forest management (MFM) for timber, non-timber forest products and environmental services is envisioned by many as a preferable alternative to timber-dominant management models. It is praised as a more equitable strategy of satisfying the demands from multiple stakeholders, an ecologically more benign harvesting approach, and a way of adding more value to forests making them more robust to conversion. MFM thus represents a common and prime management objective under the sustainable forest management (SFM) paradigm. However, its implementation has been lagging behind the expectations, particularly in the tropics. In this paper, we analyze selected MFM implementation examples to try to explain why. We scrutinize the tropical forestry debate to find that the meaning of MFM has undergone significant changes along the way, and that the topic depends heavily on the scale of inspection. Also, we examine the conditions that either favor or constrain MFM adoption. At the local scale, the factors that set the scene for multiple-use approaches to be successfully adopted are favorable governance conditions relate to land-devolution policies, effective collective institutions, and multiagent forest-management models. MFM feasibility also depends on the stage of forest transition, i.e. in society’s economic development. MFM (at the stand level) dominates in poor subsistence-oriented autarchic forest settings, it typically declines when entering capitalist stages of specialized commodity production, but may then rebound (at the landscape level) in more advanced development stages. Key factors MFM generally is up against range from intricate technical trade-offs to the economies of scale in forestry production and marketing. MFM remains a valid management alternative under specifically favorable local context conditions, especially when practiced at the landscape scale, but these conditions are less frequent than commonly assumed.